A Commentary on Thomas Berry’s Befriending the Earth, 33 Years on - McIntosh, Alastair (Religions, 2023)
The author was approached by the Passionists in the United Kingdom, a Roman Catholic order in which the ecological theologian Thomas Berry had been a priest, to seek an opinion on the continuing significance of his book, Befriending the Earth. Published in 1991, it was written in dialogue with a Jesuit colleague, Thomas Clarke. This article shares that opinion with a wider readership. Parts of it are written in a first-person manner, illustratively journeying on from where Berry left off. Thirty-three years (counted inclusively) is a generous generational span; symbolically, it is equivalent to the life of Christ, a kairos time of transition. Most notably, what has changed over that period is that climate change has landed firmly onto the environmental agenda. Significantly, Berry hardly mentioned it in this work, but in an era of Laudato Si his message of “befriending the Earth” speaks louder than ever, with prophetic poignancy.